Evaluation And Optimization Production Of Low Permeability Carbonate Reservoir By Hydraulic Fracturing In “Jaso Field” - Jakfar Sodi; Dyah Rini Ratnaningsih; Dedy Kristanto (Journal of Petroleum and Geothermal Technology, 2021)
“Jaso field” is located the South Sumatra basin, Indonesia. The lithology of this field is dominated by limestone / carbonate reservoirs with varying permeability (low / tight to high / porous). Acid Fracturing stimulation has been applied to develop this field, because in ideal conditions (with the solubility test between acid and formation > 80%) wormholes will be made in the formation to increase reservoir conductivity and productivity. However, in the Jaso oil field, in some special cases, acid injection did not provide satisfactory results for increasing well conductivity and productivity.In this thesis, we conduct research and evaluation of wells in Jaso field. For example: JS-28, JS-11 and JS-40 are oil wells in the Jaso field with low / narrow reservoir permeability and production rates. Stimulation has been carried out in the JS-28 well, but the results are still below the acid expectation even though the intermediate solubility test (solubility test) is more than 88%.Hydraulic Fracturing with the sandfracturing method (injecting sand proppant with high pressure and exceeding the gradient fracture) has been successfully applied to three wells in the Jaso Field by increasing the oil production rate by more than 100 bopd per well. With this case study, we find that the application of hydraulic fracturing (sandfracturing) with thrusters is not limited to sandstone / sandstone reservoirs, but that this method can be successfully applied to increase the conductivity and productivity of carbonate reservoirs (in special cases) taking into account several parameters of integrity. reservoir wells and characteristics.